Інцидентність та фактори ризику респіраторних ускладнень в абдомінальній хірургії у пацієнтів з ожирінням - Воротинцев, Сергій Іванович; Воротынцев, С. И.; Vorotyntsev, S. I. (My University, 2018)
Ожиріння пов’язане з такими супутніми легеневими захворюваннями, як астма, гіперреактивність дихальних шляхів, обструктивне апное сну, синдром гіповентиляції, легенева гіпертензія, що, на фоні рестриктивної фізіології легень та у поєднанні з періопераційним введенням опіоїдів, може призвести до більш високої ймовірності розвитку післяопераційних легеневих ускладнень (ПЛУ) в цій популяції. В ретроспективно-проспективному дослідженні був проведений аналіз госпітальних ПЛУ у 770 пацієнтів з ІМТ>30 кг/ м2, прооперованих на органах черевної порожнини та передній черевній стінці. Виявлено, що сумарна інцидентність ПЛУ складає від 6,1% до 7,9%, ризик іхнього розвитку збільшується при лапаротомії (відношення шансів (ВШ) 2,54; 95% довірчій інтервал (ДІ) 1,20 – 5,36; р=0,0148), недостовірно зростає у частково функціонально залежних пацієнтів (ВШ 3,54; 95%ДІ 0,96 – 13,07; р=0,0578) та у пацієнтів з МЕТ<4 (ВШ 2,46; 95%ДІ 0,53 – 11,42; р=0,2518). Таким чином, вплив ожиріння на розвиток післяопераційних респіраторних ускладнень в абдомінальній хірургії є трохи перебільшеним, а більш вагомим фактором ризику ПЛУ є лапаротомна техніка операції. Ожирение связано с такими сопутствующими легочными заболеваниями, как астма, гиперреактивность дыхательных путей, обструктивное апноэ сна, синдром гиповентиляции, легочная гипертензия, что, на фоне рестриктивной физиологии легких и в сочетании с периоперационным введением опиоидов, может привести к более высокой вероятности развития послеоперационных легочных осложнений (ПЛУ) в этой популяции. В ретроспективно-проспективном исследовании был проведен анализ госпитальных ПЛУ у 770 пациентов с ИМТ > 30 кг/м2, прооперированных на органах брюшной полости и передней брюшной стенке. Выявлено, что суммарная инцидентность ПЛУ составляет от 6,1% до 7,9%, риск их развития увеличивается при лапаротомии (отношение шансов (ОШ) 2,54; 95% доверительный интервал (ДИ) 1,20 – 5,36; р=0,0148), недостоверно возрастает у частично функционально зависимых пациентов (ОШ 3,54; 95% ДИ 0,96 – 13,07; р=0,0578) и у пациентов с МЕТ<4 (ОШ 2,46; 95% ДИ 0,53 – 11,42; р=0,2518). Таким образом, влияние ожирения на развитие послеоперационных респираторных осложнений в абдоминальной хирургии немного преувеличено, а более весомым фактором риска ПЛУ является лапаротомная техника операции. Obesity is associated with concomitant pulmonary comorbidities such as asthma, respiratory hyperreactivity, obstructive sleep apnea, hypoventilation syndrome, pulmonary hypertension, that in combination with restrictive lung physiology and perioperative opioids administration can lead to a higher probability of postoperative pulmonary complications (PPC) in this population. But recent research data is controversial. The aim of our work was to evaluate the incidence of respiratory complications after elective abdominal operations in obese patients and to determine if the level of preoperative functional status is a predictor of their development. In a retrospective-prospective study, an analysis of hospital PPC (pneumonia, reintubation, prolonged ventilator support more than 48 hours, pleural effusion, respiratory failure) was performed in 770 patients with BMI>30 kg/ m2, to whom operations on the abdominal organs and the anterior abdominal wall were carried out in the period from 2007 to 2018. The incidence of pneumonia was compared with values predicted by the ACS-NSQIP calculator. The connection of PPC with the initial level of functional status of patients (independent, partially dependent, completely dependent, MET<4, MET>4) and type of surgical intervention (laparoscopy, laparotomy, superficial surgery) were determined. Statistical processing of the results was performed using Student t-test, Mann-Whitney U-test, χ2 criterion, Fisher’s exact criterion, regression analysis. Pneumonia was observed in 2.2% – 2.5% of patients, that coincided with the predicted by ACS-NSQIP calculator risk of 2.4% [0.1; 7.2] (p>0.05). Total incidence of PPC was 7.9% in the retrospective group and 6.1% in the prospective group (p<0.05), but the percentage of separate PPC cases wasn’t significantly different between the study groups and was at the level of less than 1% for reintubation and mechanical ventilation > 48 hours, from 1% to 2.5% for pleural effusion and respiratory failure (p>0.05). More than 96% of patients in the prospective study (n = 490) were functionally independent, had good functional capacity and incidence of PPC at 5.7% level. In partially dependent patients this value increased to 17.6% (OR 3.54; 95% CI 0.96 – 13.07; р=0.0578), and in patients with MET<4 – up to 13.3% (OR 2.46; 95% CI 0.53 – 11.42; р=0.2518). Laparoscopic technique of surgery contributed to the reduction of respiratory complications probability and they occurred in 4.3% of patients, while after laparotomy PPC were recorded in 10.2% of patients (OR 2.54; 95% CI 1.20 – 5.36; р=0.0148). So, we found that the influence of obesity on the development of postoperative respiratory complications in abdominal surgery is slightly exaggerated, and the laparotomy technique of surgery is more important risk factor for PPC.
Инцидентность и факторы риска респираторных осложнений в абдоминальной хирургии у пациентов с ожирением
Incidence and risk factors of respiratory complications in abdominal surgery in obese patients
Keywords: ожиріння; респіраторні ускладнення; фактори ризику; ожирение; респираторные осложнения; факторы риска; obesity; respiratory complications; risk factors